Understanding care-seeking of pregnant women from underserved groups: a systematic review and meta-ethnography - Dasgupta, Tisha; Rayment-Jones, Hannah; Horgan, Gillian; Begum, Yesmin; Peter, Michelle; Silverio, Sergio A.; Magee, Laura A. (Frontiers in Public Health, 2025)
BackgroundDelayed or reduced antenatal care use by pregnant women may result in poorer outcomes. ‘Candidacy’ is a synthetic framework which outlines how people’s eligibility for healthcare is jointly negotiated. This meta-ethnography aimed to identify – through the lens of candidacy – factors affecting experiences of care-seeking during pregnancy by women from underserved communities in high-income countries (HICs).MethodsSix electronic databases were systematically searched, extracting papers published from January 2018 to January 2023, updated to May 2025, and having relevant qualitative data from marginalized and underserved groups in HICs. Methodological quality of included papers was assessed using the Critical Appraisal Skills Program. Meta-ethnography was used for analytic synthesis and findings were mapped to the Candidacy Framework.ResultsStudies (N = 51), with data from 1,347 women across 14 HICs were included. A total of 12 sub-themes across five themes were identified: (1) Autonomy, dignity, and personhood; (2) Informed choice and decision-making; (3) Trust in and relationship with healthcare professionals; (4) Differences in healthcare systems and cultures; and (5) Systemic barriers. Candidacy constructs to which themes were mapped were predominantly joint- (navigation of health system), health system- (permeability of services), and individual-level (appearances at health services). Mapping to Candidacy Framework was partial for seven sub-themes, particularly for individuals with a personal or family history of migration. The meta-ethnography allowed for the theory: ‘Respect, informed choice, and trust enhances candidacy while differences in healthcare systems, culture, and systemic barriers have the propensity to diminish it’.ConclusionImprovements in antenatal care utilization must focus on the joint (service-user and -provider) nature of responsibility for care-seeking, through co-production. We suggest two additional Candidacy Framework constructs: ‘intercultural dissonance’ and ‘hostile bureaucracy’, which reflect the multi-generational impact of migration on healthcare utilization and the intersection of healthcare utilization with a hostile and bureaucratic environment.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023389306, CRD42023389306.